The Determinant of Labor Supply of Informal Sector in Gowa Regency - Oktavianty, Oktavianty; Juardi, Juardi (Bulletin of Economic Studies (BEST), 2022)
This study describes the factors that influence the supply of labor in the informal sector of Somba Opu District, Gowa Regency (the street vendor sub-sector) including hours of work, capital, education level, number of dependents and gender of the supply of labor in the informal sector. This research is a type of quantitative research with an explanatory approach using primary data. Primary data obtained from questionnaires distributed to respondents, namely street vendors in Somba Opu District, Gowa Regency as many as 47 respondents. This data was tabulated with the excel program and processed with the help of SPSS version 24 software. The results of the study through the multiple linear regression analysis method showed that there was a significant effect on the variables of working hours, capital and gender on the supply of labor in the informal sector. Meanwhile, the variables of education level and number of dependents did not significantly affect the supply of labor in the informal sector. Keywords: Labor Supply, Working Hours, Capital, Education Level, Informal Sector